Marketing of Non-timber forest Products: An Economic Analysis - Dubey, Parag (Indian Journal of Marketing, 2006)
Marketing plays a crucial role in developed as well as developing economies in creating demand for and supply of various goods and services (Kolter, 1998). A marketing system cannot be considered efficient and effective unless it caters to the needs of different segments of the society. It is unfortunate that the marketing system in India is not well developed and as a result, a large section of the society particularly in tribal areas are deprived of the benefits that accrue from an efficient marketing system (Rao, 1988).